Make Your Own Deep Inferior Epigastric Artery Perforator Flap: Perforator Delay Improves Deep Inferior Epigastric Artery Perforator Flap Reliability. Issue 11 (November 2019) - Shakir, Sameer; Spencer, Amy B.; Kozak, Geoffrey M.; Jablonka, Eric M.; Kanchwala, Suhail K.
Abstract : Background: Abdominal-based autologous breast reconstruction remains a conflict between blood supply and donor site complication. Optimizing esthetics and minimizing recovery and postoperative pain add further complexity. We present a 2-stage technique of deep inferior epigastric artery perforator flap reconstruction to (1) reliably harvest single-vessel flaps while minimizing fat necrosis, (2) decrease abdominal wall morbidity, and (3) improve breast and donor site esthetics. Methods: Female subjects presenting between August 2017 and January 2019 to the senior surgeon for abdominal-based breast reconstruction were included. After mastectomy, the subjects underwent subcutaneous placement of tissue expanders and in situ selection of a low, centrally located perforator based on preoperative computed tomographic angiography imaging through an infraumbilical "T" incision with ligation of all other perforators and superficial system. Subjects underwent tissue expander explant and flap transfer at a second stage. Results: One hundred thirty-five subjects undergoing 215 free flaps met criteria. Mean age and body mass index were 52.1 years and 29.3 kg/m 2, respectively. Seven perforator complications (3.3%) occurred with 2 (0.9%) total and 5 (2.3%) partial flap losses. There were 20 (14.8%) readmissions and 26 (19.3%) reoperations. Breast complications included arterial thrombosis (0.5%), venous congestion (1.9%), and fat necrosis (5.1%). The mastectomy skin flap necrosis rate decreased from 14.9% to 2.3% following staged reconstruction. Abdominal donor site complications included delayed healing (11.1%), seroma (5.9%), and hematoma (2.2%). Conclusions: The 2-stage delayed deep inferior epigastric artery perforator flap technique represents a safe, efficacious modality to allow for reliable harvest of single-vessel flaps with low rates of fat necrosis while improving donor site esthetics and morbidity.